1990
DOI: 10.1021/bi00453a025
|View full text |Cite
|
Sign up to set email alerts
|

Sequential resonance assignment and secondary structure determination of the Ascaris trypsin inhibitor, a member of a novel class of proteinase inhibitors

Abstract: The solution conformation of the Ascaris trypsin inhibitor, a member of a novel class of proteinase inhibitors, has been investigated by nuclear magnetic resonance spectroscopy. Complete sequence-specific assignments of the 1H NMR spectrum have been obtained by using a number of two-dimensional techniques for identifying through-bond and through-space (less than 5-A) connectivities. Elements of regular secondary structure have been identified on the basis of a qualitative interpretation of the nuclear Overhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…In a different way, Ascaris-type SPIs from animal venoms were deduced to inhibit the proteases of their preys or predators, thereby protecting other toxic peptides to avoid degradation and inactivation. Almost all Ascaristype SPIs have a common structural characteristic with four short ␤-strands arranged in two approximately perpendicular ␤-sheets and stabilized by five disulfide bridges: Cy-I-Cys-VII, Cys-II-Cys-VI, Cys-III-Cys-V, Cys-IV-Cys-X, and Cys-VIIICys-IX (24). Consistent with the previous results, Sj7170 shares the similar structural characteristic with Ascaris-type SPIs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a different way, Ascaris-type SPIs from animal venoms were deduced to inhibit the proteases of their preys or predators, thereby protecting other toxic peptides to avoid degradation and inactivation. Almost all Ascaristype SPIs have a common structural characteristic with four short ␤-strands arranged in two approximately perpendicular ␤-sheets and stabilized by five disulfide bridges: Cy-I-Cys-VII, Cys-II-Cys-VI, Cys-III-Cys-V, Cys-IV-Cys-X, and Cys-VIIICys-IX (24). Consistent with the previous results, Sj7170 shares the similar structural characteristic with Ascaris-type SPIs.…”
Section: Discussionsupporting
confidence: 88%
“…U87 cells were treated with rSj7170 at various concentrations (0, 2, 4, 6, 8, and 10 M) for 48 h and with 10 M for various timings (24,48, and 72 h). The results showed that rSj7170 significantly increased cell proliferative capacity in a dose-and time-dependent manner, compared with control cells (Fig.…”
Section: Sequence Analysis Of Sj7170 a Member Of The Ascaris-typementioning
confidence: 99%
“…As part of the parasite defense strategy, Ascaris roundworms secrete a series of inhibitors to target digestive and immunerelated host proteases, among others pepsin, trypsin, chymotrypsin/elastase, cathepsins, and metallocarboxypeptidases (MCPs) (9)(10)(11)(12)(13)(14)(15)(16). MCPs are zinc-containing exoproteases that catalyze the hydrolysis of C-terminal amino acids from proteins and peptides.…”
mentioning
confidence: 99%
“…Different serine protease inhibitors have been identified from various parasitic nematodes, including Ascaris suum, A. lumbricoides (Gronenborn, Nilges, Peanasky, & Clore, 1990;Peanasky et al, 1984, b), Anisakis simplex (Morris & Sakanari, 1994) Ancylostoma caninum, A. ceylanicum, A. duodenale (Mieszczanek, Harrison, & Cappello, 2004;Rios-Steiner, Murakami, Tulinsky, & Arni, 2007;Jin et al, 2011), Trichuris suis (Rhoads, Fetterer, & Hill, 2000), and Onchocerca volvulus (Ford et al, 2005;Lustigman et al, 1992) where they were believed to have a variety of functions to protect the nematode from intestinal serine proteases or to be involved in molting and development of the nematodes.…”
Section: Discussionmentioning
confidence: 99%